Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Pada Materi Perkalian Bilangan Cacah Untuk Meningkatkan Hasil Belajar Di Kelas III SD GMIT Namosain - Pade, Ruth Stefiany G; Wara Sabon Dominikus; Adam Bol Nifu Benu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled "The Application of Contextual Teaching and Learning Model on Multiplication of Whole Numbers to Improve Learning Outcomes in Grade III of GMIT Namosain Elementary School" is motivated by the low learning outcomes of grade III students of GMIT Namosain Elementary School on multiplication of whole numbers. This study aims to determine the improvement in student learning outcomes after the application of the Contextual Teaching and Learning (CTL) model on multiplication of whole numbers in grade III of GMIT Namosain Elementary School. This research is a Classroom Action Research (CAR) which consists of planning, action implementation, observation, and reflection stages. The research subjects were 27 grade III students of GMIT Namosain Elementary School. The data collection techniques used were observation and tests using observation sheets and test questions as research instruments. The data analysis technique used was quantitative data analysis by calculating the average value and percentage of learning completion. The results of the study indicate that the application of the Contextual Teaching and Learning (CTL) learning model can improve student learning outcomes on multiplication of whole numbers. The learning completion percentage increased from 15% in the pre-cycle to 63% in the first cycle and 89% in the second cycle. The average student score also increased from 33.7 in the pre-cycle to 63 in the first cycle and 80.7 in the second cycle. Furthermore, teacher activity increased from 68.74% to 91.02%, while student activity increased from 56.66% to 90%.